ANALISA UNJUK KERJA TURBIN GAS PLTG DUAL FUEL SYSTEM (STUDY KASUS DI PT. XXX SIAK) - Veny Selviyanty; Aris Fiatno (Jurnal Teknik Industri Terintegrasi, 2020)
PT. XXX serviced the Kawasaki GPB80 gas turbine with the latest data on the use of gas fuel in gas turbine unit 6 on average 32,028 liters / day and the use of diesel fuel in turbine unit 3 is 39,111 liters / day. This research was conducted with field observations and literature studies. Field observations obtained the following data: pressure, temperature at predetermined points, engine generator, the surrounding environment and required supporting data. The specific fuel consumption obtained in unit 6 gas turbines using diesel fuel is 0.049 l / kW hour. turbine efficiency obtained in unit 3 gas turbines using diesel fuel is 9.02%. Decreased Torque performance in unit 3 gas turbine of 6186 Nm caused by an average T2 temperature of 85 0C before entering the combustion chamber so that the combustion process is incomplete in the combustion chamber resulting in thermal efficiency in the unit 3 gas turbine not proportional to the Specific Fuel Consumtion or usage diesel fuel against the effective power produced. The specific fuel consumption in unit 3 gas turbine is 0.06 l / kW.h while the unit 6 gas turbine is 0.04 l / k.W.h.